The role of kurds in the conflicts and military coups against the mamluk authority - Ahmad, Dilman; Salem, Lulav (Humanities Journal of University of Zakho, 2024)
The Mamluk era is regarded as one of the important eras in Islamic history. This is because the Mamluks became the main force in the Islamic world during that time. and that period was marked by numerous revolutions and coups against the ruling power. The Kurds, particularly the Ayyubids, played a great role in governance prior to the Mamluk era. It is known that the role of the Kurds remained similar in the Mamluk era, but to a lesser extent. The Kurds were actively involved in the events of that era, and occasionally, they were the focal point of the events. On several occasions, Kurds were part of the internal conflicts of the Mamluks to seize power from them and restore the power to the Ayyubid rule. The Kurds consistently held a belief that the Mamluks had unjustly robbed the power them and that they should advocate its restoration to its rightful owners.